The Effect of Work Motivation, Workplace Communication, and Work Environment on Traffic Police Performance Through Work Discipline - Tri Pepri Alfiyan; Feti Fatimah; Astrid Maharani (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to analyze the effect of work motivation, work communication, and work environment on the performance of traffic police officers (Satlantas Polresta Banyuwangi) with work discipline as an intervening variable. The background of this study is based on the inconsistency of employee performance, particularly in aspects of discipline, communication, and coordination that are not yet optimal. This research uses a quantitative approach with data collection through questionnaires. The population consists of all members of Satlantas Polresta Banyuwangi, with a census sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with WarpPLS 8.0 software.The results show that work motivation and work environment have a positive and significant effect on work discipline and employee performance. Work communication affects work discipline but does not have a significant effect on performance. Work discipline significantly affects performance and is able to mediate the effect of work motivation and work environment on performance, but it does not mediate the effect of work communication on performance. The implication of this study indicates that improving employee performance can be achieved by strengthening work motivation, improving the work environment, and enhancing work discipline as a key factor